Effect of carbon precursors and pore expanding reagent on ordered mesoporous carbon for resorcinol removal. (June 2017) - Chao, Bing; Konggidinata, Mas Iwan; Lin, Lu; Zappi, Mark; Gang, Daniel Dianchen
Graphical abstract: Highlights: Adsorption performances of OMCs made by different carbon precursors and different amounts of pore expanding reagent were evaluated. The increase in the amount of boric acid led to a bigger pore size but higher tendency of pore collapse. The effect of specific surface area of OMC on resorcinol removal was more significant than that of the surface chemical properties. Maximum adsorption capacity was found to be 64 mg/g for OMC-2 made of sucrose with boric acid ratio of 2. Abstract: Ordered mesoporous carbons (OMCs) with well-controlled pore structures have recently attracted much attention because of their potential applications as adsorbents. The specific surface area and surface chemistry of OMCs have been considered as two of the most important factors that affect their adsorption capacity for organic compounds. The objectives of this study were to compare the adsorption capacities of OMCs for resorcinol removal by using different carbon precursors (acrylic acid, sucrose and glucose) and optimizing the pore structure by using boric acid as the pore expanding reagent via hard template method. Among the three carbon precursors, sucrose demonstrated the highest adsorption performance for resorcinol removal and hence, was selected as the carbon precursor to evaluate the effect of pore expanding reagent. The tailored pore sizes ranging from 4.7 nm to 11.0 nm were obtained by varying the ratio of boric acid to sucrose from 0 to 4. It was observed that OMC with boric acid to sucrose ratio of 2 yielded the highest adsorption capacity (64 mg/g). OMC structure was characterized by small angle X-Ray Diffraction (XRD), Transmission Electron Microscopy (TEM), surface area and porosimetry analyzer, Fourier Transfer Infrared spectroscopy (FT-IR), elemental analysis, Boehm titration and adsorption study. The results suggested that the effect of specific surface area of OMC on resorcinol removal was more significant than that of the surface chemical properties.